Effects of the NYU Caregiver Intervention-Adult Child on Residential Care Placement - Gaugler, Joseph E. (Oxford University Press, 2013)
Purpose: This study determined whether the NYU Caregiver Intervention, adapted in Minnesota for adult child caregivers (NYUCI-AC), prevented or delayed residential care placement for persons with dementia. Design and Methods: A single-blinded randomized controlled trial design was used. One hundred and seven adult child caregivers of persons with dementia were randomly assigned to the NYUCI-AC treatment group who received individual and family counseling, support group referral, and ad hoc consultation or a contact control group. Participants were asked to complete structured assessments quarterly during Year 1 and every 6 months thereafter for a minimum of 2 years. Results: Two thirds (66%) of adult child caregivers in the control condition admitted their parent to a residential care setting compared with 37% in the treatment condition. Logistic regression and Cox proportional hazards models found that NYUCI-AC participants were significantly less likely (p < .05) to admit their parents to a residential care setting and delayed their parents’ time to admission significantly longer (228.36 days longer on average) than those in the control group. Implications: The multicomponent NYUCI-AC offered adult children the psychosocial support required to continue providing care to cognitively impaired parents at home.